Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Sure, let's solve the system of equations using the elimination method step-by-step:
Given system of equations:
1) [tex]\( x - y = 5 \)[/tex]
2) [tex]\( x + y = 3 \)[/tex]
Step 1: Add the two equations to eliminate [tex]\( y \)[/tex].
When we add equations (1) and (2), we get:
[tex]\[ (x - y) + (x + y) = 5 + 3 \][/tex]
This simplifies to:
[tex]\[ x - y + x + y = 8 \][/tex]
Combining like terms, we have:
[tex]\[ 2x = 8 \][/tex]
Step 2: Solve for [tex]\( x \)[/tex].
Divide both sides by 2:
[tex]\[ x = \frac{8}{2} \][/tex]
So:
[tex]\[ x = 4 \][/tex]
Step 3: Substitute [tex]\( x = 4 \)[/tex] back into one of the original equations to solve for [tex]\( y \)[/tex].
Let's use equation (1):
[tex]\[ x - y = 5 \][/tex]
Substituting [tex]\( x = 4 \)[/tex]:
[tex]\[ 4 - y = 5 \][/tex]
Step 4: Solve for [tex]\( y \)[/tex].
Subtract 4 from both sides:
[tex]\[ -y = 1 \][/tex]
Multiplying both sides by -1:
[tex]\[ y = -1 \][/tex]
Therefore, the solution to the system of equations is:
[tex]\[ x = 4 \quad \text{and} \quad y = -1 \][/tex]
The ordered pair [tex]\((4, -1)\)[/tex] represents the solution.
Given system of equations:
1) [tex]\( x - y = 5 \)[/tex]
2) [tex]\( x + y = 3 \)[/tex]
Step 1: Add the two equations to eliminate [tex]\( y \)[/tex].
When we add equations (1) and (2), we get:
[tex]\[ (x - y) + (x + y) = 5 + 3 \][/tex]
This simplifies to:
[tex]\[ x - y + x + y = 8 \][/tex]
Combining like terms, we have:
[tex]\[ 2x = 8 \][/tex]
Step 2: Solve for [tex]\( x \)[/tex].
Divide both sides by 2:
[tex]\[ x = \frac{8}{2} \][/tex]
So:
[tex]\[ x = 4 \][/tex]
Step 3: Substitute [tex]\( x = 4 \)[/tex] back into one of the original equations to solve for [tex]\( y \)[/tex].
Let's use equation (1):
[tex]\[ x - y = 5 \][/tex]
Substituting [tex]\( x = 4 \)[/tex]:
[tex]\[ 4 - y = 5 \][/tex]
Step 4: Solve for [tex]\( y \)[/tex].
Subtract 4 from both sides:
[tex]\[ -y = 1 \][/tex]
Multiplying both sides by -1:
[tex]\[ y = -1 \][/tex]
Therefore, the solution to the system of equations is:
[tex]\[ x = 4 \quad \text{and} \quad y = -1 \][/tex]
The ordered pair [tex]\((4, -1)\)[/tex] represents the solution.
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.